Proceedings of the 2015 IEEE/ACM International Symposium on Nanoscale Architectures (NANOARCH´15) 2015
DOI: 10.1109/nanoarch.2015.7180596
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of radiation-induced soft errors in FinFET SRAMs under process variations beyond 22nm

Abstract: New CMOS technologies such as SOI or FinFET are expected to enhance SRAM radiation-induced soft error rates thanks to a reduction on the charge collected as the devices get smaller. In this work we analyze how the radiation hardening capabilities of SRAMs are affected when process variations are considered by simulating cells using a predictive FinFET technology.The results show that even if the average critical charge to which SRAM cells are vulnerable is enhanced by process variations, its widened spread lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…It is known from the literature that radiation can lead to soft errors in FinFETs even at ground level [2], [6]. A number of works performed a comparative analysis regarding SEEs between FinFET and other technologies (conventional bulk CMOS and SOI) [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known from the literature that radiation can lead to soft errors in FinFETs even at ground level [2], [6]. A number of works performed a comparative analysis regarding SEEs between FinFET and other technologies (conventional bulk CMOS and SOI) [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the proximity of connections and the reduced supply voltage, FinFET-based SRAMs are becoming more susceptible to SEUs, even at ground level [6]. Traditionally, the major sources of radiation-induced soft errors at ground level or flight altitudes are: (1) alpha particles originated by the radioactive contamination existing in the packaging [13], [14]; (2) the high-energy neutrons from cosmic radiation (generating secondary reactions); and (3) the interaction of cosmic ray thermal neutrons with devices containing borophosphosilicate glass [14].…”
Section: Introductionmentioning
confidence: 99%
“…While in the subthreshold, even larger current pulse causes the flip due to the smaller node capacitance. The authors in [87,88] showed the difference in the charge collection property using a 3D device model for bulk/planner and FinFET. The result shows how different devices with different physical structure (e.g., bulk, FinFET, FDSOI) with various This is a critical challenge for ULP biomedical applications where a person is required to travel at different altitudes and the neutron flux increasing with altitude [5].…”
Section: Resultsmentioning
confidence: 99%
“…A reduced I ON results in a weaker feedback path for the storage node in a crossed couple bitcell. Since the first report of cosmic rays causing failures in 1975 space applications, a significant amount of work has been done, from device structure [86][87][88]90] to different protection schemes [91][92][93]. The device like FDSOI makes device robust against the particle strike by structure while Deeply Depleted Channel (DDC) [30] reduces doping concentration in the channel helps SEU reduction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation